The Open Innovation in Science research field: a collaborative conceptualisation approach. Issue 2 (7th February 2022) - Beck, Susanne; Bergenholtz, Carsten; Bogers, Marcel; Brasseur, Tiare-Maria; Conradsen, Marie Louise; Di Marco, Diletta; Distel, Andreas P.; Dobusch, Leonhard; Dörler, Daniel; Effert, Agnes; Fecher, Benedikt; Filiou, Despoina; et al.
ABSTRACT: Openness and collaboration in scientific research are attracting increasing attention from scholars and practitioners alike. However, a common understanding of these phenomena is hindered by disciplinary boundaries and disconnected research streams. We link dispersed knowledge on Open Innovation, Open Science, and related concepts such as Responsible Research and Innovation by proposing a unifying Open Innovation in Science (OIS) Research Framework. This framework captures the antecedents, contingencies, and consequences of open and collaborative practices along the entire process of generating and disseminating scientific insights and translating them into innovation. Moreover, it elucidates individual-, team-, organisation-, field-, and society‐level factors shaping OIS practices. To conceptualise the framework, we employed a collaborative approach involving 47 scholars from multiple disciplines, highlighting both tensions and commonalities between existing approaches. The OIS Research Framework thus serves as a basis for future research, informs policy discussions, and provides guidance to scientists and practitioners.